Financial Literacy Level of Business Actors in Pasar Tilil, Bandung City - Sabila, Silsi; Setiawan , Hayun; Yuniarsih, Yuyun (Yayasan Sinergi Kawula Muda, 2024)
Financial inclusion has become a critical issue in the economic development of a country. It encompasses access to, usage of, and understanding of financial products and services available within society. Researchers conducted a pre-survey at Tilil Market in Bandung City and found a phenomenon of low financial literacy among business players. This study aims to analyze the percentage of financial literacy among business players in Tilil Market, Bandung City. This research adopts a descriptive quantitative approach using survey methods and data collection through questionnaires. Data analysis employs descriptive statistical analysis with validity tests to assess questionnaire validity and reliability tests to gauge reliability. SPSS version 23 software aids in data analysis. Based on the findings, the average scores for each dimension of financial literacy among business players in Tilil Market, Bandung City are as follows: basic knowledge of personal finance (41.96%), understanding of savings and loans (54.94%), comprehension of insurance (55.17%), and understanding of investments (17.24%). The final results of descriptive statistical analysis on financial literacy levels among business players in Tilil Market, Bandung City indicate an overall percentage of 39.41%, with the majority falling into the category of low financial literacy